Idol's Dam and Power Plant on the Yadkin River. - Jones, Frank (Forsyth County Public Library, 1930)
Photo made in the 1930s.
Idol's Dam and Power Plant on the Yadkin River. Photo shows the interior of the power plant.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth